1974
DOI: 10.1128/iai.9.3.571-575.1974
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Immunity in Typhus Infections IV. Failure of Chicken Embryo Cells in Culture to Restrict Growth of Antibody-Sensitized Rickettsia prowazeki

Abstract: Rickettsia prowazeki , pretreated with typhus immune human serum, readily infects, and grows in, chicken embryo cells in culture. This finding is similar to those of previous studies which showed that typhus rickettsiae, pretreated with immune serum, grow in cells of the yolk sac of embryonated hen eggs and in the cells of the midgut of the human body louse. In contrast, identically treated typhus rickettsiae were destroyed by human macrophages in culture. Collectively, these observations seem to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

1975
1975
2011
2011

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…It is suggested that antibody-sensitized rickettsiae are capable of entering and replicating within the guinea pig's endothelial cells. This possibility is supported by the demonstration that antibodies which prepare R. prowazekii for destruction by macrophages (1,5) do not prevent this parasite from entering or replicating within chicken embryo cells (16), cells which are not professional phagocytes.…”
Section: Discussionmentioning
confidence: 99%
“…It is suggested that antibody-sensitized rickettsiae are capable of entering and replicating within the guinea pig's endothelial cells. This possibility is supported by the demonstration that antibodies which prepare R. prowazekii for destruction by macrophages (1,5) do not prevent this parasite from entering or replicating within chicken embryo cells (16), cells which are not professional phagocytes.…”
Section: Discussionmentioning
confidence: 99%
“…These data, along with those of Cohn et al (5) and Wisseman et al (24,(26)(27)(28), allow the beginnings of a model of rickettsial invasion of host cells. Our results suggest that each native rickettsia adheres specifically to the target cell surface, where it triggers the host endocytic mechanism, and the adherent rickettsia is rapidly phagocytized.…”
Section: Walker and Winklermentioning
confidence: 53%
“…We have utilized a new, radioactive assay to characterize the invasion of L cells by R. prowazeki. This assay offers several advantages over the microscopic assays previously used (5,24,26,28) in studies on rickettsial invasiveness. Microscopic assessment of rickettsial invasion into cultured cells is tedious, requiring subjective examination of hundreds of individual host cells to insure reliability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the growth of virulent rickettsiae which have been treated with specific antisera prior to infection is inhibited in macrophage cells and macrophagelike cell lines (1,5,6,10). In contrast, specific antiserum-treated rickettsiae of either strain grow normally in fibroblasts (10,17), indicating that the combination of the antiserum and a macrophage-specific factor is necessary for antirickettsial activity. Macrophagelike cells are used since they are similar to human macrophages in their interaction with R. prowazekii, are clonal and subject to less heterogeneity, and undergo a respiratory burst and since a mutant cell line exists that has lost this ability.…”
mentioning
confidence: 99%